Two temperate Earth-mass planets orbiting the nearby star GJ 1002 - Suárez Mascareño, Alejandro; Quirrenbach, Andreas; Henning, Thomas; Kaminski, Adrian (Astronomy and astrophysics, 2023)
We report the discovery and characterisation of two Earth-mass planets orbiting in the habitable zone of the nearby M-dwarf GJ 1002 based on the analysis of the radial-velocity (RV) time series from the ESPRESSO and CARMENES spectrographs. ...